Cylindrical Planetary Nebulae. I. Flow from an Irradiated Ring - Vincent Icke (Galaxies, 2022)
Many bipolar nebulae with a pronounced cylindrical shape, such as Henize 3-401, show no indication whatsoever of interaction between a disk and a stellar wind, or a jet on the nebular axis. I propose that the disk that is observed at the base of the bipolar is itself the source of the outflow. In particular, I assume that irradiation from the central star causes the disk to evaporate. I have performed numerical hydrodynamical calculations of outflows driven by evaporation of a pseudo-barotropic ring around a hot central star. The first results show that the outflow shapes are cylindrical, and the internal structures are similar to what is observed in some of these nebulae. Since shape is only the first step in the assessment of a model, synthetic observations should be made. For the moment I merely verify that the scalar quantities observed in the archetypical cylindrical nebula Hen 3-401 can be accommodated in my models.